New Trends in Differential and Difference Equations and Applications - Minhós, Feliz (2020)
This is a reprint of articles from the Special Issue published online in the open-access journal Axioms (ISSN 2075-1680) from 2018 to 2019 (available at https://www.mdpi.com/journal/axioms/special issues/differential difference equations).